CUSTOMER INTENTION TO STAY WITH BANKS: THE ROLE OF VIRTUAL SERVICE - Wong, Mei Foong; Lim, Chow Yeng (International Journal of Supply Chain Management, 2018)
Identifying the success factors that contribute to customer satisfaction and loyalty are the crucial and it is a continuous process in order for firms to stay competitive. This paper examines the factors that determine the customer satisfaction and loyalty and its causal effects using a theoretical model. The research model consists of four exogenous latent constructs, namely service quality, perceived value, brand image and online banking quality. Customer satisfaction is the mediator and the endogenous variable is intention to stay. Data relating to the constructs were collected from 12 banks' customers located in the Klang Valley by using convenience sampling method, and subjected to Structural Equation Modeling (SEM) analysis. The hypothesized structural model fits the data well. The results disclose that perceived value and online banking quality have a direct and indirect effect on intention to stay, while service quality and brand image have only an indirect effect on intention to stay.